Serum 25-Hydroxyvitamin D, Calcium, Phosphorus, and Electrocardiographic QT Interval Duration: Findings from NHANES III and ARIC - Zhang, Yiyi (Endocrine Society, 2011)
CONTEXT: Disturbances in 25-hydroxyvitamin D, calcium, and phosphorus concentrations have been associated with increased risks of total and cardiovascular mortality. It is possible that changes in electrocardiographic QT interval duration may mediate these effects, but the association of 25-hydroxyvitamin D, phosphorus, and calcium concentrations with QT interval duration has not been evaluated in general population samples. OBJECTIVE: The objective of the study was to evaluate the association of 25-hydroxyvitamin D, phosphorus, and calcium concentrations with QT interval duration in two large samples of the U.S. general population. DESIGN: This study included cross-sectional analyses the Third National Health and Nutrition Survey (NHANES III) and the Atherosclerosis Risk in Communities (ARIC) study. SETTING: The study was conducted in the general community. PATIENTS OR OTHER PARTICIPANTS: Patients included 7,312 men and women from NHANES III and 14,825 men and women from the ARIC study. INTERVENTIONS: Serum 25-hydroxyvitamin D, total and ionized calcium, and inorganic phosphorus were measured in NHANES III, and serum total calcium and inorganic phosphorus were measured in ARIC. MAIN OUTCOME MEASURE: QT interval duration was obtained from standard 12-lead electrocardiograms. RESULTS: In NHANES III, the multivariate adjusted differences in average QT interval duration comparing the highest vs. the lowest quartiles of serum total calcium, ionized calcium, and phosphorus were −3.6 msec (−5.8 to −1.3; P for trend = 0.005), −5.4 msec (−7.4 to −3.5; P for trend <0.001), and 3.9 msec (2.0–5.9; P for trend <0.001), respectively. The corresponding differences in ARIC were −3.1 msec (−4.3 to −2.0; P for trend <0.001), −2.9 msec (−3.8 to −1.9; P for trend <0.001), and 2.3 msec (1.3–3.3; P for trend <0.001). No association was found between 25-hydroxyvitamin D concentrations and QT interval duration. CONCLUSIONS: In two large samples of the general population, QT interval duration was inversely associated with the serum total and ionized calcium and positively associated with serum phosphorus.